THE ANALYSIS OF ENGLISH READING TEXTS BASED ON NATIONAL CHARACTER AND CULTURAL EDUCATION ON COURSE BOOK FOR THE TENTH GRADE AT THE STATE OF SENIOR HIGH SCHOOL IN PAMEKASAN - Akbar Syahbana; Mochammad Rizqi Adhi Pratama (OKARA: Jurnal Bahasa dan Sastra, 2017)
This study is based on the phenomenon around us that has many inappropriate contents of books especially in reading texts. Whereas, there is regulation from the government which should insert the value of National Character and Cultural Education as character building in all elements of education. The author took the course book that was widely used by many English teachers at the state of Senior High School in Pamekasan, totally nine schools. Then, descriptive qualitative was used as research design. The purposes analyzed what values were existed in reading texts and how reading texts had reflected the values. Furthermore, this study used descriptive qualitative to analyze the findings. Based on the result, the author found 13 values which were inserted in 17 reading texts, but the rests were not; besides,  there were several ways of reading texts to reflect values.